The processed food revolution in African food systems and the double burden of malnutrition - Reardon, Thomas; Tschirley, David; Liverpool-Tasie, Lenis Saweda O.; Awokuse, Titus; Fanzo, Jessica; Minten, Bart; Vos, Rob (Elsevier, 2021)
African consumers have purchased increasing amounts of processed food over the past 50 years. The opportunity cost of time of women and men has increased as more of them work outside the home, driving them to buy processed food and food prepared away from home to save arduous home-processing and preparation labor. In the past several decades, this trend has accelerated with a surge on the supply side of the processing sector and small and medium enterprises (SMEs) and large private companies making massive aggregate investments. Packaged, industrialized, ultra-processed foods and sugar-sweetened beverages (SSBs) are a growing proportion of the processed food consumed. Also, in the past several decades, overweight and obesity have joined the long-standing high levels of stunting and wasting among children and extreme thinness among women of childbearing age. Together these phenomena have formed a double burden of malnutrition (DBM). The DBM has emerged as an important health problem in sub-Saharan Africa. The rise of the DBM and the increase in ultra-processed food consumption are linked. makers face a dilemma. On the one hand, purchases of processed food are driven by long-term factors, such as urbanization, increased income, and employment changes, and thus cannot change the pursuit of convenience and labor-saving food. Moreover, much processed food, like packaged milk, is a boon to nutrition, and the processed food system is a major source of jobs for women. On the other hand, the portion (some 10–30%) of processed food that is ultra-processed is a public health challenge, and must address its detrimental effects on disease burden. The global experience suggests that double duty actions are most important as are selected policies focused on healthy weaning foods for addressing stunting and taxes on SSBs, nutrition labeling, and other measures can steer consumers away from unhealthy ultra-processed foods to addressing obesity and possibly child nutrition and stunting. We recommend that African governments consider these options, but that the current extreme fragmentation of the processing sector, consisting of vast numbers of informal SMEs in sub-Saharan Africa, and the limited administrative/implementation capacity of many African governments require pursuing this path only gradually.